2016
DOI: 10.1037/fam0000132
|View full text |Cite
|
Sign up to set email alerts
|

Marital violence and coparenting quality after separation.

Abstract: Research has identified multiple predictors of coparenting quality, but few studies have investigated how intimate partner violence (IPV) affects divorcing couples’ coparenting relationships. We addressed this question in a sample of 154 mothers with different marital IPV experiences. Mothers were recruited within four months of a divorce filing and completed two interviews three months apart. At Time 1, mothers reported on violence and coercive control during marriage, and postseparation behavioral (e.g., par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 42 publications
(82 reference statements)
1
31
1
2
Order By: Relevance
“…It is possible that the careful screening by both CWS and the SFI staff limited the CWS families to a less high-risk subsample. Nevertheless, our study joins an expanding literature demonstrating that it is possible to include at least some couples referred to CWS for domestic violence (Hardesty et al, 2016), child abuse, or neglect in a couples group intervention once those problems have been addressed and that a coparenting intervention has the potential for positive benefits for parents and their children, in contrast with single-sex programs that have shown limited success (Babcock, Green, & Robie, 2004;Stith, McCollum, Amanor-Boadu, & Smith, 2012).…”
Section: Implications For Practicementioning
confidence: 78%
See 1 more Smart Citation
“…It is possible that the careful screening by both CWS and the SFI staff limited the CWS families to a less high-risk subsample. Nevertheless, our study joins an expanding literature demonstrating that it is possible to include at least some couples referred to CWS for domestic violence (Hardesty et al, 2016), child abuse, or neglect in a couples group intervention once those problems have been addressed and that a coparenting intervention has the potential for positive benefits for parents and their children, in contrast with single-sex programs that have shown limited success (Babcock, Green, & Robie, 2004;Stith, McCollum, Amanor-Boadu, & Smith, 2012).…”
Section: Implications For Practicementioning
confidence: 78%
“…We acknowledge the controversy that exists surrounding a couple's systems approach to treatment when intimate partner violence or child abuse has been identified (Mahraj, ; Stith & McCollum, ). However, a comprehensive review of studies indicates that working with couples conjointly is efficacious and appropriate in some situations (Karakurt, Whiting, Esch, Bolen, & Calabrese, ), such as when situational violence rather than coercive control is involved (Hardesty, Crossman, Khaw, & Raffaelli, ). With careful monitoring for safety concerns, our intervention supported couples work on communication issues, negative attributions, and self‐control of aggression.…”
Section: The Present Studymentioning
confidence: 99%
“…Alternatively, these two DV fathers may have progressed over time from a negative, blaming view of their ex‐partner's parenting and a lack of insight, to more normative post‐separation co‐parenting. It is also possible that these fathers may be distinguished from the other DV fathers on the basis of their history of DV perpetration, as might be suggested by research with mothers that found associations between post‐separation co‐parenting and the severity/type of previous violence (Hardesty and Ganong, ; Hardesty et al, , ). Even so, it is a limitation of this study that we do not know enough about these two fathers to infer whether a progression to healthier co‐parenting took place over time, whether their ex‐partners would describe similarly positive co‐parenting, or whether progression could potentially take place for other DV fathers.…”
Section: Discussionmentioning
confidence: 99%
“…. (Christopher, Umemura, Mann, Jacobvitz, & Hazen, 2015;Hardesty, Crossman, Khaw, & Raffaelli, 2016), .…”
Section: ( )mentioning
confidence: 99%